Recurrence of cervical intraepithelial neoplasia grades 2 or 3 in HIV-infected women treated by large loop excision of the transformation zone (LLETZ) - Russomano, Fábio; Reis, Aldo; Camargo, Maria José; Grinsztejn, Beatriz; Tristão, Maria Aparecida (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Women infected by HIV are more likely to have cervical cancer and its precursors. Treatment of the precursor lesions can prevent this neoplasia. The aim of this study was to assess the likelihood of recurrent cervical intraepithelial neoplasia grades 2 or 3 (CIN 2-3) in HIV-infected women, compared with HIV-negative women, all treated by large loop excision of the transformation zone (LLETZ). DESIGN AND SETTING: A cohort study in Instituto Fernandes Figueira, Fundação Oswaldo Cruz (IFF-Fiocruz), Rio de Janeiro. METHOD: 55 HIV-positive and 212 HIV-negative women were followed up after LLETZ for CIN 2-3 (range: 6-133 months). RESULTS: The incidence of recurrent CIN 2-3 was 30.06/10,000 woman-months in the HIV-positive group and 4.88/10,000 woman-months in the HIV-negative group (relative risk, RR = 6.16; 95% confidence interval, CI: 2.07-18.34). The likelihood of recurrence reached 26% at the 62nd month of follow-up among the HIV-positive women, and remained stable at almost 0.6% at the 93rd month of follow-up among the HIV-negative women. We were unable to demonstrate other prognostic factors relating to CIN recurrence, but the use of highly active antiretroviral therapy (HAART) may decrease the risk of this occurrence among HIV patients. CONCLUSION: After LLETZ there is a higher risk of recurrence of CIN 2-3 among HIV-positive women than among HIV-negative women. This higher risk was not influenced by margin status or grade of cervical disease treated. The use of HAART may decrease the risk of this occurrence in HIV patients.